A comparative analysis on safety and efficacy of telmisartan and ramipril in treatment of hypertension in a tertiary care hospital - Gulzar, Wajid; Dar, Mudasir Manzoor; Singh, Amritpal; Masoodi, Peer Samiq; Samreen, Shah; Jyoti, Uma (International Journal of Research in Medical Sciences, 2026)
Background: Hypertension is a major global health challenge and an important risk factor for cardiovascular disease. Angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs) are commonly used first-line antihypertensive agents. This study evaluated the safety and efficacy of telmisartan and ramipril in patients with hypertension at a tertiary care hospital. Methods: This prospective observational study included 113 adult patients with hypertension who received either telmisartan (n=56) or ramipril (n=57). Pre- and post-treatment systolic (SBP) and diastolic blood pressure (DBP) were assessed. Efficacy was evaluated by achievement of target blood pressure, while safety was assessed based on adverse drug reactions. Statistical analysis was performed using the chi-square test. Results: Both treatments significantly reduced SBP and DBP. Post-treatment SBP shifted mainly to 120-140 mmHg, while DBP improved to 76-85 mmHg. Target blood pressure was achieved more frequently with telmisartan (96.4%) than ramipril (80.7%) (χ2=6.862, p<0.05). Telmisartan was also associated with fewer cases of cough and greater improvement in symptoms such as headache and fatigue. Conclusions: Both telmisartan and ramipril effectively reduced blood pressure. However, telmisartan was more effective in achieving target blood pressure and showed better tolerability with fewer adverse effects, suggesting it may be a preferable option, particularly for patients intolerant to ACE inhibitors.